Predicting growth of the healthy infant using a genome scale metabolic model - Avlant Nilsson (Nature Portfolio, 2017)
Systems biology: Feeding breast milk to a computer model of a baby A research group headed by Prof. Jens Nielsen from Chalmers University of Technology built a computer model of a newborn baby (0–6 months). The computer model simulated a baby’s metabolism of breastmilk, predicting growth in weight, fat and height. An optimization algorithm was used to identify the best flow of nutrients through the metabolic network, from milk to biomass. The researchers used the model to determine if the availability of any nutrient limits growth, e.g., essential amino acids. They found that all nutrients are available with good margin and that growth is limited by the production and consumption of energy. The model may be useful to better understand how malnutrition leads to stunted growth, which affects 165 million children worldwide. Additionally it represents a major advancement toward a complete computer model of the living human.